International Entrepreneurship in Bottom of the Pyramid Markets – Overcoming institutional constraints - Hanni, Helena (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Bottom of the pyramid (BoP) markets are an underserved market of approximately four billion people living on under $5 a day in four regional areas: Africa, Asia, Eastern Europe and Latin America. According to estimations, the BoP market forms a $5 trillion global consumer market. Despite the potential of BoP markets, companies have traditionally focused on serving the markets of developed countries and ignored the large customer group at the bottom of the pyramid. The BoP approach as first developed by Prahalad and Hart in 2002 has focused on multinational corporations (MNCs), which were thought of as the ones who should take responsibility in serving the customers at the bottom of the pyramid. This study challenges this proposition and gives evidence that also smaller international new ventures – entrepreneurial firms that are international from their birth, can be successful in BoP markets. BoP markets are characterized by a number of deficiencies in the institutional environment such as strong reliance on informal sector, lack of infrastructure and lack of skilled labor. The purpose of this study is to increase the understanding of international entrepreneurship in BoP markets by analyzing how international new ventures overcome institutional constraints in BoP markets and how institutional uncertainty can be exploited by solving institutional problems. The main objective is divided into four sub objectives. • To describe the opportunities and challenges BoP markets present • To analyze the internationalization of INVs to BoP markets • To examine what kinds of strategies international entrepreneurs use to overcome institutional constraints • To explore the opportunities institutional uncertainty offers for INVs Qualitative approach was used to conduct this study and multiple-case study was chosen as a research strategy in order to allow cross-case analysis. The empirical data was collected through four interviews with the companies Fuzu, Mifuko, Palmroth Consulting and Sibesonke. The results indicated that understanding of the wider institutional environment improves the survival prospects of INVs in BoP markets and that it is indeed possible to exploit institutional uncertainty by solving institutional problems. The main findings were that first-hand experience of the markets and grassroots levels of information are the best assets in internationalization to BoP markets. This study highlights that international entrepreneurs with limited resources can improve the lives of people at the BoP with their business operations and act as small-scale institutional entrepreneurs contributing to the development of the institutional environment of BoP markets.

Bottom of the pyamid markets (BoP markets) , eli – ”elintasopyramidin pohjan markkinat” ovat noin neljän miljardin, alle viidellä dollarilla päivässä elävien ihmisten muodostama markkina-alue pääasiassa Afrikassa, Aasiassa, Etelä-Amerikassa ja Itä-Euroopassa. Yritykset ovat perinteisesti keskittyneet kehittyneisiin markkinoihin ja sivuuttaneet BoP- markkinoiden valtavan potentiaalin. Arvioiden mukaan BoP- markkinat muodostavat viiden triljoonan euron markkinat. Tämä tutkimus kyseenalaistaa BoP- näkemyksen kehittäjien, Prahaladin ja Hartin (2002) näkemyksen siitä, että BoP- markkinoilla vain suurilla monikansallisilla yrityksillä olisi mahdollisuus menestyä ja osoittaa, että myös pienemmät ”syntymästään kansainväliset yritykset” (international new venture) voivat menestyä BoP- markkinoilla. BoP- markkinat ovat haasteellinen toimintaympäristö, jossa erityisesti institutionaaliset haasteet, kuten markkinoiden epävirallisuus, ihmisten osaamattomuus ja infrastruktuurin puutteellisuus tekevät liiketoiminnan harjoittamisen hankalaksi. Tämän tutkimuksen tarkoitus on analysoida, miten syntymästään kansainväliset yritykset selviytyvät institutionaalisista haasteista ja tarkastella institutionaalisen epävarmuuden tarjoamia liiketoimintamahdollisuuksia. Tutkimus vastaa seuraaviin alakysymyksiin: • Minkälaisia mahdollisuuksia ja haasteita BoP- markkinoilla on? • Miten syntymästään kansainväliset yritykset kansainvälistyvät BoP- markkinoille? • Millaisia strategioita kansainväliset yrittäjät käyttävät institutionaalisten haasteiden voittamiseen? • Millaisia liiketoimintamahdollisuuksia institutionaalinen epävarmuus tarjoaa? Tutkimus suoritettiin kvalitatiivisin menetelmin, ja monitapaustutkimus valittiin tutkimustavaksi. Empiirinen aineisto kerättiin haastattelemalla seuraavaa neljää yritystä: Fuzu, Mifuko, Palmroth Consulting ja Sibesonke. Empiirinen aineisto osoitti, että institutionaalisen ympäristön ymmärrys on ensisijaisen tärkeää ja että toisaalta epävarmuus tarjoaa myös liiketoimintamahdollisuuksia yrityksille, jotka ratkaisevat institutionaalisia ongelmia liiketoiminnallaan. Tutkimustulokset osoittavat, että ruohonjuuritason kokemus markkinoista on tärkeintä kansainvälistyessä BoP- markkinoille. Tutkimus korostaa, että kansainväliset yrittäjät voivat parantaa ihmisten elämää BoP- markkinoilla liiketoiminnallaan ja toimia pienimuotoisesti institutionaalisina yrittäjinä edesauttaen instituutioiden kehitystä BoP- markkinoilla.